2015
DOI: 10.1096/fj.14-266825
|View full text |Cite
|
Sign up to set email alerts
|

Histatin-1, a histidine-rich peptide in human saliva, promotes cell-substrate and cell-cell adhesion

Abstract: Histatins (Hsts) are histidine-rich peptides exclusively present in the saliva of higher primates. In this study, we explored the effects of Hsts on cell-substrate and cell-cell adhesion. Histatin (Hst)-1 caused a significant (>2-fold) increase (EC 50 = 1 mM) in the ability of human adherent cells to attach and spread, even in conditions that impaired cell spreading. Other tested Hsts did not stimulate cell spreading, indicating a specific effect of Hst1. The effect of Hst1 on cell-cell adhesion was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
53
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 38 publications
11
53
0
Order By: Relevance
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
“…A promising candidate cell‐targeting agent to promote cell–substrate interactions is histatin‐1 (Hst1), a member of a large histidine‐rich salivary peptide family. Our previous findings show that Hst1 can significantly promote the attachment, spreading, and migration of various cell types including epithelial, endothelial, and osteogenic cells . Our recent data confirm that Hst1 can promote the spreading of osteogenic cells on both bio‐inert glass and titanium surface , which suggests a promising application potential of Hst1 in the cell‐based bone tissue engineering.…”
supporting
confidence: 65%
“…Moreover, it has been reported that an unidentified GPCR pathway (Galpha-i linked) is critical for histatin peptide effects on cell migration [20]. Studies in other tissues on MAPK pathways have demonstrated an increase in cell-substrate and cell-cell adhesion with increased trans-epithelial resistance [21] and independence from p38 MAPK (proliferative) pathway inhibitors [7]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that histatins (Hst1 and Hst2) are the main factors in human saliva responsible for skin and oral keratinocyte and fibroblast migration, suggesting a role in wound closure [1416]. Hst1 is also able to enhance cell-substrate adhesion and cell-cell interaction [17, 18]. …”
Section: Introductionmentioning
confidence: 99%